The implication of reversal burden proof on corruption criminal act (Research, Society and Development, 2020)
The polemic of the ratification of KPK (Corruption Eradication Commission) Constitution indicated the good intentions of government as well as people in society through their respective perceptions which in conclusion whether the KPK is getting stronger or become weaker. The aim of this analysis is to examine on the implication of reversal burden proof system on corruption criminal act in Indonesian Law. Reversal of the burden proof as determined in the PTPK Law and the 2003 KAK Law leaves problems in its implementation, through normative legal research with the study of laws and comparisons, something new is obtained which is a guideline for judges in giving verdicts regarding the results of verification of assets and actions. Implications of proven or unproven acts and assets of the defendant through reversing the burden of proof of criminal criminal behavior which is greatly affects the received sanction by the defendant which include imprisonment penalties, criminal sanctions for fines and additional criminal sanctions in the form of returning state financial losses.